Paracetamol-induced fixed erythema. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2019)
The diagnosis of fixed drug eruption is usually easy, but its pathogenesis is not entirely clear. Constitutional factors, intermittent administration of the same drug, which is more often taken during an infection of the upper respiratory tract and also the pathogenicity of the responsible drug play a possible role. This is confirmed by the fact that up to 20 years ago in our pediatric series fixed erythema was frequent and its cause was usually feprazone. When the latter went out of fashion and was supplanted by paracetamol, fixed erythema became exceptional (1) and paracetamol became the most frequent cause. The oral exposure test with half a dose of the suspected drug, practiced at least 4 weeks after the last flare up (2) is the most appropriate test to ascertain the cause, except in very extensive cases, where skin tests or lymphocyte stimulation are used.